Geomorphological patterns of remotely sensed methane hot spots in the Mackenzie Delta, Canada - Latha Baskaran; Clayton Elder; A Anthony Bloom; Shuang Ma; David Thompson; Charles E Miller (Environmental Research Letters, 2022)
We studied geomorphological controls on methane (CH _4 ) hotspots in the Mackenzie Delta region in northern Canada using airborne imaging spectroscopy collected as part of the Arctic Boreal Vulnerability Experiment. Methane emissions hotspots were retrieved at ∼25 m ^2 spatial resolution from a ∼10 000 km ^2 NASA’s Next Generation Airborne Visible/Infrared Imaging Spectrometer survey of the Mackenzie Delta acquired 31 July–3 August 2017. Separating the region into the permafrost plateau and the lowland delta, we refined the domain wide power law of CH _4 enhancements detected as a function of distance to standing water in different ecoregions. We further studied the spatial decay of the distance to water relationship as a function of land cover across the Delta. We show that geomorphology exerts a strong control on the spatial patterns of emissions at regional to sub-regional scales: compared to methane hotspots detected in the upland, we find that methane hotspots detected in the lowland have a more gradual power law curve indicating a weaker spatial decay with respect to distance from water. Spatial decay of CH _4 hotspots in uplands is more than 2.5 times stronger than in lowlands, which is due to differences in topography and geomorphological influence on hydrology. We demonstrate that while the observed spatial distributions of CH _4 follow expected trends in lowlands and uplands, these quantitatively complement knowledge from conventional wetland and freshwater CH _4 mapping and modeling.